Clinical Supervision by School Principals in Enhancing the Performance of Islamic Religious Education Teachers at Bakalan Nguntoronadi Wonogiri State Elementary School - Edy Muslimin; Meti Fatimah; Muhammian Sobe Arashi; Nafilah Khusnul Awwaliyah (Didaktika: Jurnal Kependidikan, 2024)
The purpose of this study was to determine the extent of the principal's clinical supervision in improving the performance of Islamic Religious Education teachers at SD Negeri Bakalan Nguntoronadi Wonogiri. Clinical supervision is important to be done by the principal because it is to see the learning process of the teacher in the classroom. To achieve the objectives of this study, a qualitative approach was used with the principal and Islamic religious education teachers as the main informants. Data were collected through observation, structured interviews and documentation as well as the results of relevant literature. Data analysis uses interactive analysis, namely data collection, data reduction, data presentation, and inference. The results showed that, first, by instilling Islamic religious education teachers' understanding of clinical supervision, including basic concepts of clinical supervision, collaboration and shared learning, influence on professional development, and cultural and contextual perspectives. Second, the principal's clinical supervision strategies include: Identifying common needs and goals, classroom observation and feedback, creating a structured monitoring plan, developing lesson plans, periodic monitoring and evaluation, and training and professional development. However, this study found that Islamic religious education teachers do not participate in activities such as workshops, seminars, or other training that support the improvement of teaching skills. This is because the cost is borne by the teacher and there is no financial support from the local education office.